Herpetología patagónica : II. Notas sobre la distribución geográfica del género Diplolaemus - Cei, José Miguel Alfredo María (1971)
The geographical distribution of the patagonian iguanids Diploiatmus darwini and D. bibroni is actualized. The occidental andean distribution of the first species and the oriental patagonian area of the second one is emphasized.